Hubungan Self Care dengan Quality of Life pada Pasien Gagal Jantung di Rsu Prof Dr. R. D. Kandou Manado - Adipati, Devita Yanti; Paat, Calvin Toar Christo; Malara, Reginus Tertius (Mapalus Nursing Science Journal, 2025)
Background Heart failure is one of the causes of death in the world. Patients with this condition experience a decrease in the heart muscle's ability to pump blood effectively and meet the body's oxygen needs. As a result, the patient's quality of life decreases, so self-care efforts are needed to help improve their quality of life. Objective This study aims to determine the relationship between Self Care and Quality of Life in heart failure patients. Method The research uses quantitative methods with a cross-sectional approach. The research sample consisted of 85 heart failure patients, selected using a purposive sampling technique. Results The Pearson correlation test resulted in p = 0.032 (p value < 0.05) so it can be concluded that there is a significant relationship between Self Care and Quality of Life with the strength of the correlation (r = 0.232) which is in the weak category with a positive correlation direction. Conclusion There is a significant relationship between Self Care and Quality of Life in heart failure patients at Prof. Dr. R.D. Kandou Hospital Manado.